Complete plastome sequence of Torenia benthamiana Hance (Linderniaceae), an endemic herb in South China. Issue 2 (3rd July 2019) - Cheng, Xia-Lan; Liu, Yi-Ming; Wang, Hong-Xin; Li, Hai-Li; Chen, Yan; Wang, Li-Yun
Abstract: Torenia benthamiana Hance is an endemic plant species distributed in southern China. In this study, we report and characterize the complete plastid genome sequence of T. benthamiana in order to provide genomic resources helpful for promoting its conservation and garden utilization. The complete plastome is 153, 526 bp in length and contains the typical quadripartite structure of angiosperm plastome, including two inverted repeat (IR) regions of 24, 638 bp, a large single-copy (LSC) region of 85, 417 bp, and a small single-copy (SSC) region of 18, 833 bp. The plastome contains 114 genes, consisting of 80 unique protein-coding genes, 30 unique tRNA gene, and 4 unique rRNA genes. The overall A/T content in the plastome of T. benthamiana is 62.40%. The complete plastome sequence of T. benthamiana will provide a useful resource for the conservation and garden utilization of this species as well as for the phylogenetic studies of Linderniaceae.